Spiritual Care Intervention on Emotional Regulation in Caregivers with Schizophrenic : A Systematic Review - Maulidiyah Junnatul Azizah Heru; Rizki Fitryasari; Hendy Muagiri Margono (STRADA : Jurnal Ilmiah Kesehatan, 2020)
Schizophrenic client caregivers are faced with various problems caused by the abnormal behavior of schizophrenic clients that can trigger stress. To determine the effectiveness of spiritual care in improving the emotional regulation of caregiver clients with schizophrenia. The sources of the articles used were obtained from searches through the Scopus database Google Scholar, Science Direct, and Proquest. The search for articles is limited from 2015 to 2020. The keywords used are "spiritual care", "Emotional Regulation" "Caregiver". This systematic review uses 15 articles that fit the inclusion criteria. The spiritual care intervention from the reviewed research is very significant in increasing the emotional regulation of the caregiver in schizophrenic clients. Spiritual care strategy can increase emotional regulation and calm attitude so that it will have a good impact on the recovery process for schizophrenic clients. Keywords: spiritual care; emotion regulation; caregiver